Evaluation of the potential of polyhydroxybutyrate-co-hydroxyvalerate bi-layered scaffolds for skin tissue engineering - Zonari, A. A. C. (2012)
Polyhydroxybutyrate-co-hydroxyvalerate (PHB-HV) is natural-based polyester produced by microorganisms under unbalanced growth con- ditions. This polymer is known for its biocompatibility and biodegrad- ability and has been explored for tissue engineering approaches. The aim of this work was to create a bi-layered construct, based on PHB- HV, for skin tissue replacement. The PHB-HV bi-layered scaffold was produced taking into consideration the two main skin strata, the epi- dermis and the dermis. For the epidermal fraction, a membrane was developed using a solvent cast approach, while freeze-drying was used to obtain the dermal fraction. The two structures were combined to obtain a scaffold that has a thin compact surface (epidermal) and a por- ous structure (dermis), as confirmed by scanning electron microscopy (SEM) and micro-CT analysis. Each layer of the scaffold, epidermal and dermal, was respectively seeded with human keratinocytes (Kc) and human dermal fibroblasts (Fb). The characterization by SEM con- firmed the typical morphology of Kc and Fb on the expected surfaces. Calcein-AM and DNA quantification showed that both type of cells remained viable along the experiment and were able to attach and pro- liferate on the respective seeding layers. In conclusion, the developed PHB-HV scaffolds have shown suitable properties to sustain the co-cul- ture of Kc and Fb, which constitutes a solid base for further work to demonstrate its potential for skin replacement.